Catalogue of Richardiidae (Diptera: Tephritoidea) and abundance and populational fluctuation of two Richardiid species (Diptera: Richardiidae) in anthropized areas of Atlantic Forest in southeastern Brazil - Pádua, Thiago Henrique dos Reis (2025)
The Family Richardiidae (Diptera: Tephritoidea) comprises 35 genera and 197 described species, and is mostly distributed in the Neotropical region. This study present a catalog of Richardiidae, which historically faces challenges in their classification due to low morphological diversity and a complex and confusing taxonomic history. Here, an updated catalog of Richardiidae is provided, including synonyms, geographic distribution, information on type specimens, their condition, and the scientific collections in which they are deposited. The information was systematically organized, including detailed protocols of label transcriptions and standardized abbreviations. The present study aims to consolidate and update the taxonomic knowledge of Richardiidae, summarizing the information about species. Indeed, a survey was conducted to evaluate the abundance and population fluctuation of two Richardiidae species in areas of the Atlantic Forest with varying levels of anthropization on the \"Luiz de Queiroz\" campus, Piracicaba, SP. Then, multilure traps baited with putrescine and ammonium acetate were set up in four areas (Agroforestry, Central Area, Riparian Forest, and Preserved fragment) from April/2019 to March/2020. A total of 120 specimens were collected and identified as Richardiodes trimaculata Henning, 1937 and Richardia teevani Curran, 1934. Richardiodes trimaculata (n = 93) was the most abundant species, predominating in less disturbed areas, while Ri. Teevani (n = 27) showed lower abundance and was more sensitive to disturbance. Both species presented population peak in the dry season (JulySeptember), suggesting seasonal adaptation, which differs from other saprophagous dipterous. Our results highlight the importance of preserved remains for conservation of Richardiidae species and show that those species can be sampled using multilure traps.